Chemistry :science of change - Oxtoby, David W.; Freeman, Wade A.; Block, Toby F. ([S.l.] : Cengage Learning, 1997)
The organization of the text treats chemistry as an experimental subject by beginning with observable, macroscopic chemistry and later moving to the quantum mechanical theory that provides the underpinning of modern chemistry.
Keywords: chemistry